A Cell for Controllable Formation and In Operando Electrochemical Characterization of Intercalation Materials for Aqueous Metal‐Ion Batteries. Issue 12 (16th August 2019) - Marzak, Philipp; Moser, Philipp; Schreier, Siegfried; Scieszka, Daniel; Yun, Jeongsik; Schneider, Oliver; Bandarenka, Aliaksandr S.
Abstract: Recently, aqueous metal‐ion batteries have attracted significant attention, as they can provide rather efficient and safe solutions with regard to large‐scale renewable energy storage applications. However, better fundamental understanding of the electrode and electrolyte materials for these devices is necessary to advance their performance. The research methodology for well‐known types of batteries, such as lithium‐ion batteries, relies on numerous available cell designs and protocols. Fundamental research in the field of aqueous metal‐ion batteries, on the contrary, still requires the development of new, original, and versatile cells as well as procedures to improve the efficiency and informative power of experiments. In this work, a concept for the research cell design dedicated to the aqueous metal‐ion batteries is presented, enabling advanced electrochemical characterization of model electrode materials (including the mass changes of the active electrodes). Electrodes based on Prussian blue analogs, which are state‐of‐the‐art electrode materials for aqueous Na‐ion batteries, are used to demonstrate the concept. Abstract : Comprehensively understanding electrode and electrolyte materials permits an efficient elaboration of better batteries. A new design for electrochemical cells dedicated to aqueous metal‐ion batteries facilitates fast progress in fundamental research in this new technological field. Advanced research routines involving numerous experimental steps, and combining multiple in situ procedures and in operando techniques become possible while using only a single setup.